Effects of Floium ginkgo extract and tertram ethypyrazine sodium chloride injection on expression of inflammatory cytokines and cerebral infarction - Zhang, Qingna; Yuan, Chunhui; Liu, Jingyan; Li, Pengfei; Dong, Zhuo (Cellular and Molecular Biology, 2020)
This experiment was carried out to observe and analyze the effect of floium ginkgo extract and tertram ethypyrazine sodium chloride injection in patients with cerebral infarction. A total of 200 patients diagnosed with cerebral infarction were enrolled in the study. They were randomly divided into a research group and control group, each containing 100 patients. The control group was given routine treatment measures while the research group was given floium ginkgo extract and tertram ethypyrazine sodium chloride injection on the basis of routine treatment. The therapeutic effects of the two groups were observed and compared. After implementing different treatment schemes, the levels of MMP-9, SOD, CBV and CBF in the research group were significantly higher than those in the control group, p<0.05. The research group was lower in hs-CRP, MDA, MTT, TTP and TNF-Î± as compared with the control group, p<0.05. In terms of the quality of life of the two groups after six months of treatment, the scores of various indicators in the research group were all significantly superior, p<0.05. Conclusion: The treatment of cerebral infarction patients with floium ginkgo extract and tertram ethypyrazine sodium chloride injection can significantly improve the therapeutic effect, which is a relatively ideal treatment.